An Assessment of HCG from Day 2 Spent Embryo Culture Media and its Relation to Embryo Developmental Potential in Females Undergoing IVF Using Different Ovulation Triggers (HCG, Decapeptyl Alone or Dual Trigger) - Ali Abed, Israa; Sraibet Abbod, Muayad; Ali Jwad, Mufeda (International Journal of Psychosocial Rehabilitation, 2020)
Infertility is one of the major medical difficulties in the world caused by genetic or epigenetic causes, or both, which has led to constant research and studies in the field of assisted reproductive technology. Several stimulation protocols are available for controlled ovarian hyperstimulation in in vitro fertilization and intracytoplasmic sperm injection. To compare the effect of HCG and dual triggering for final oocyte maturation on HCG level in embryo spent culture media and its effect on embryo development and quality. In order to assess the health and developmental ability of an individual embryo, the need for noninvasive processes in addition to morphological assessment of the embryo has increased, like HCG level in culture media.